THEORY-GROUNDED MODEL OF USERS’ PERCEPTION TOWARDS NATIVE ADVERTISEMENT (Mokslo taikomieji tyrimai / Applied Research, 2022)
The growing native advertising acceptance throughout different social media (e. g., Facebook, Twitter, Reddit, Instagram, YouTube) suggests that native advertising is here to stay. Previous research focuses on the persuasion knowledge effect on ad perceptions, disclosure effect towards persuasive intent recognition and congruency effect on ad nativeness. However, there is a lack of research that focuses on attitudes towards native advertisements. Furthermore, previous research has mixed findings towards the ad transparency effect. Thus, the problem of this study is to determine whether ad congruency and transparency influence attitudes towards native ads, which in turn impacts the attitude towards the brand. The study aims to construct a model testing attitudes towards native ads in ad congruency and transparency settings. The objectives of the study are as follows: to analyse the scientific literature referring to the persuasion knowledge model regarding native advertising recognition and perceptions; identify factors that influence native ad transparency and congruency and how it impacts attitudes towards native ads. The persuasion knowledge model explains why users perceive the covert nature of native advertisements negatively. Nowadays, internet users experience native advertisements in social media, online news portals and viewing websites. Based on previous research, the overall perception of native advertising can be attributed to two aspects – ad transparency and congruence. Previous research methods on native advertising mostly focused on manipulating various variables to test which ad elements most impact positive attitudes towards it. The variables identified in the literature analysis are as follows: ad transparency, ad congruence, attitudinal/conceptual/dispositional persuasion knowledge, and attitude towards ads. The proposed research model is greatly influenced by the persuasion knowledge model proposed by Friestad & Wright (1994), which was expanded by S. C. Boerman et al. (2012), having introduced dispositional, conceptual, and attitudinal persuasion knowledge concepts.
Keywords: native advertisement; brand attitudes; Persuasion knowledge model (PKM)